1999
DOI: 10.1007/s004280050429
|View full text |Cite
|
Sign up to set email alerts
|

20q13.2 Amplification in intraductal hyperplasia adjacent to in situ and invasive ductal carcinoma of the breast

Abstract: The 20q13 region harboring recently described putative oncogenes is frequently amplified in invasive ductal carcinoma (IDC). The aim of this study was to examine the 20q13 copy number in intraduct hyperplasia (IH), atypical duct hyperplasia (ADH), and ductal carcinoma in situ (DCIS) adjacent to IDC. In 5 patients, comparative genomic hybridization (CGH) after laser microdissection revealed 20q13 amplification in four of five cases of IH, in all of three cases of IH with atypia, all five of DCIS, and all five o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 8 publications
0
34
1
Order By: Relevance
“…Apart from ADH and ALH, which bear remarkable morphological and molecular resemblance to welldifferentiated DCIS and LCIS, respectively, the other non-obligate/premalignant lesions have proven more difficult to characterize and establish their actual position along the pathways [2,16,[60][61][62][63][64][65][66][67]. Interestingly, ADH and low-grade DCIS show identical immunoprofiles and low numbers of chromosomal abnormalities, comprising recurrent loss of 16q (see ref 2 and refs cited therein).…”
Section: Hyperplasias and Columnar Cell Changementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from ADH and ALH, which bear remarkable morphological and molecular resemblance to welldifferentiated DCIS and LCIS, respectively, the other non-obligate/premalignant lesions have proven more difficult to characterize and establish their actual position along the pathways [2,16,[60][61][62][63][64][65][66][67]. Interestingly, ADH and low-grade DCIS show identical immunoprofiles and low numbers of chromosomal abnormalities, comprising recurrent loss of 16q (see ref 2 and refs cited therein).…”
Section: Hyperplasias and Columnar Cell Changementioning
confidence: 99%
“…However, its role in the multi-step model of breast carcinogenesis has been questioned (for a review see ref 2 and refs cited therein) [2,5,15,16,[64][65][66][67]. The morphological features and immunoprofile of HUTs are in stark contrast with those of the accepted precursors, since they are composed of a mixed population of cell types with a variable proportion of ER, PgR-positive luminal cells and myoepithelial/basal marker-positive cells.…”
Section: Hyperplasias and Columnar Cell Changementioning
confidence: 99%
“…On the basis of molecular data, primarily loss of heterozygosity and comparative genomic hybridization studies, a number of authors have shown clonal chromosomal aberrations in usual ductal hyperplasia, though they occur at lower frequency, with fewer alterations per lesion, as compared with atypical ductal hyperplasia, ductal carcinoma in situ, and invasive carcinomas; other studies have shown identical chromosomal changes in usual ductal hyperplasia and accompanying invasive carcinoma. 37,[42][43][44][45][46][47][48] Investigation of activating point mutations in PIK3CA, AKT and other cell signaling pathways in usual ductal hyperplasia, and other breast precursor lesions such as atypical ductal hyperplasia and columnar cell change, should be instructive in further characterizing the divergent molecular and histologic pathways of breast cancer evolution.…”
mentioning
confidence: 99%
“…However, the exact timing of the majority of molecular genetic events during carcinogenesis and their correlation with defined histopathological stages are largely unknown. (1)(2)(3)(4)(5)(6)(7). Invasive ductal carcinoma (IDC) of the breast is the result of a multistep process, beginning with ductal hyperplasia and followed by atypical ductal hyperplasia, ductal carcinoma in situ (DCIS), invasive ductal carcinoma and metastatic disease (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%